Extensive cardiopulmonary resuscitation of preterm neonates at birth and mortality and developmental outcomes. (February 2019) - Fischer, Nicole; Soraisham, Amuchou; Shah, Prakesh S.; Synnes, Anne; Rabi, Yacov; Singhal, Nalini; Ting, Joseph Y.; Creighton, Dianne; Dewey, Deborah; Ballantyne, Marilyn; Lodha, Abhay; ,; et al.
Abstract: Objective: To compare mortality and neurodevelopmental outcomes of extremely low gestational age neonates who received delivery room extensive cardiopulmonary resuscitation (DR-CPR) to those who did not require DR-CPR. Methods: Preterm neonates born at <29 weeks' gestational age between January 2010 and September 2011 and assessed at Canadian Neonatal Follow-Up Network centers were studied. Neonates who received DR-CPR were compared to those who did not require DR-CPR using univariate and multivariable analyses. The primary outcome was a composite of mortality or any neurodevelopmental impairment at 18 to 24 months corrected age defined as the presence of any one or more of the following: cerebral palsy; Bayley-III cognitive, language, or motor composite scores <85 on any one of the components; sensorineural/mixed hearing loss or unilateral or bilateral visual impairment. Secondary outcomes were the individual components of the composite outcomes. Results: Of the 2760 neonates born, 173 were excluded and remaining 2587 eligible neonates were included in our study. Of these 2068 had outcome data (80%) of whom 190 (9.2%) received DR-CPR. DR-CPR was independently associated with mortality or neurodevelopmental impairment (adjusted odds ratio [aOR] 1.76; 95% CI 1.21–2.55) and mortality alone (aOR1.94; 95% CI 1.33–2.83). DR-CPR was also associated with increased odds of motor impairment (aOR 2.03; 95% CI 1.28–3.23). Conclusion: In extremely low gestational age neonates, DR-CPR was associated with higher odds of the composite outcome of mortality or neurodevelopmental impairment, mortality alone, and lower motor scores at 18 to 24 months' corrected age.